The Relationship between Economic Value Added (EVA®) and Market Value Added (MVA) With Reported Earnings: An Empirical Research Of 40 Listed Companies In Indonesia Stock Exchange For The Year 2004-2007 - Pratiwi Putri Wibowo; Ruben Garcia Berasategui (Journal of Applied Finance & Accounting, 2008)
This study was made to examine the relationship between Economic Value Added (EVA®) and Market Value Added (MVA) with the reported earnings. Thus, the purpose is to gain better understanding in the use of EVA and MVA in relation to the reported earnings in certain purposes from different regression models. With the sample of 40 Indonesian listed companies in Indonesia Stock Exchange from year 2004 to 2007, the hypothesis testing is used to find the relationships among variables. The author use formula for calculating EVA and MVA to be use in four models of regression analysis against reported earnings. This study found evidence in the relationships between EVA and MVA with reported earnings, and the highest correlation among the models is relationship within the same year period, which can be used for evaluation purposes. Only the relationship of the EVA in the previous year and reported earnings changes is proved not significant. Still, MVA is more significant in explaining its relationship with reported earnings rather than EVA. The author concludes that in general, Indonesian listed companies still produces negative EVA. On the other hand, while the EVA and MVA are proved to have correlation with reported earnings, the result for EVA is lower than MVA. Therefore, there is still not enough evidence that EVA can be used to explain the reported earnings effectively other than MVA.